تأثير التضخم الركودي على النمو الاقتصادي في الدول النامية للمدة 1984-2002 - د. فواز جارالله; هيثم أكرم سعيد (PROSPECTIVE RESEARCHES, 2023)
The theoretical frame of the present study has Presented a detailed presentation for the nature of the dispute existed among the intellectual trends that reject Keynes thoughts and opinions and Philips and his supporters' theory represented by the schools of stagflation in the capitalist economics and the reflections of the opinions of each school on the economics and the developing countries. In addition, the study attempts to explain the inflation line in the developing countries and the relation between this variable and the economic growth, and to present a brief view about the unemployment situation in those countries as well, The importance of the present research comes out from the verification of its hypothesis which says that the stagflation has an influence not only on capitalist economics but also on the developing economics. The research hypothesizes that both the internal and external factors have their influential role in showing the stagflation phenomenon for the countries under investigation and its reflection on the economic growth in those countries. The study has shown that the stagflation in its outset has positively influenced some of the sample countries. Nevertheless, that influence has been in decreased rates. That has been obvious in Argentina, Brazil, Costa Rica, Uruguay, as well as Chile after dropping the variable of time. The study has also concluded that the stagflation in its outset has a not shown its effect on Venezuela and Ecuador because these countries are distinguished among the sample countries in that they have benefited from the oil incomes to cut down the effect the stagflation on the economic growth.